2011
DOI: 10.1063/1.3565198
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of planar-type Ni/vacuum/Ni tunnel junctions based on ferromagnetic nanogaps using field-emission-induced electromigration

Abstract: Planar-type Ni/vacuum/Ni tunnel junctions based on ferromagnetic nanogaps were fabricated by field-emission-induced electromigration in an approach that we call “activation.” In the activation method, we were simply and easily able to control the tunnel resistance of the nanogaps from 1.6 MΩ to 169 kΩ by adjusting only the magnitude of the field emission current. The resistance of the junction formed by the activation was varied by applying external magnetic fields, and the magnetoresistance (MR) ratio was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Recently, Araidai et al have found using first-principles calculations based on the densityfunctional theory (DFT) that surface atom under field emission (FE) evaporates with lower fields than the typical strength of field evaporation without FE. Then, FE-assisted surface atoms evaporate in the same direction as the electron flow [13], which is in good agreement with the direction of moving atoms controlled by the "activation" [11,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Recently, Araidai et al have found using first-principles calculations based on the densityfunctional theory (DFT) that surface atom under field emission (FE) evaporates with lower fields than the typical strength of field evaporation without FE. Then, FE-assisted surface atoms evaporate in the same direction as the electron flow [13], which is in good agreement with the direction of moving atoms controlled by the "activation" [11,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 80%
“…In addition, one can facilely obtain the planar-type ferromagnetic nanogaps with Ni/Vacuum/Ni tunnel junctions using the activation with a voltage source [14]. Furthermore, we have also investigated the successful control of the nanogaps by directly adjusting the field emission current with a current source [15].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…We call this "activation" method. The activation method is based on moving the atoms induced by the Fowler-Nordheim (F-N) field emission current passing through the nanogaps between source and drain electrodes [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In the activation procedures, it is expected that the moved atoms accumulate within the gaps and play the dual role of reducing the gap width and forming SETs islands [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%